Bacterial intrauterine infection and acute inflammatory changes of the placenta, fetal membranes and umbilical cord - Kochoski, Goran; Spasova R; Tanturovski, Mile; Lazarova-Stojoska, Aleksandra; Spasevska, Liljana (Macedonian Association of Anatomists and Morphologists, 2019)
Introduction: Preterm delivery is a clinical syndrome with multifactorial etiology and it is considered to be one of the most challenging issues of contemporary perinatology. Intrauterine infections play one of the leading roles in the development of this clinical entity, but the prevalence of microbial invasion and the type of microorganisms associated with this condition are still a subject of debate. Material and methods: We conducted a cross-sectional study at the University clinic for obstetrics and gynecology in Skopje. One hundred and fifty (150) patient with clinical signs of preterm delivery between 24+0-37+0 g.w. were included. For microbiological analysis, samples were taken using standard cotton swab, from the maternal side of the placenta at the border between the placental disk and fetal membranes. For histopathologic analysis, placentas were collected in transport container and sent to Institute of pathology. Samples for histopathologic analysis were provided from the following zones: border amnion-chorion, chorionic plate, umbilical cord and fetal membranes. The results were considered statistically significant if p<.05. Results: Microbiological analysis of provided samples showed a presence of bacteria in 61/150 (40.7%) of the patients. Results from the analysis of the inflammatory changes of the placenta, fetal membranes and umbilical cord showed a higher frequency of maternal and fetal inflammatory response of any stage or grade in patients with positive microbiological findings. No statistically significant difference was found for the maternal inflammatory response of any stage or grade (p=.09), but the difference in the distribution of the fetal inflammatory response of any stage or grade was found to be statistically significant (p=.006). Intensity of the fetal inflammatory response was higher in patients with positive cultures, and there was a statistically significant association between the positive microbiological findings and the stages and grades of fetal inflammatory response. Conclusion: Positive microbiological findings increase the risk for histopathologically proven acute chorioamnionitis in patients with preterm delivery. In this category of patients there is a significantly higher frequency of acute inflammatory changes of the umbilical cord, with higher frequency of the higher stages and grades of fetal inflammatory response and statistically significant association between the positive culture and the intensity of the fetal inflammatory response.
Keywords: microbial invasion; intraamniotic infection; chorioamnionitis; placentitis; funisitis